Molecular markers of Ryadg gene and serological assay reveal potato virus Y (PVY) resistance in the tetraploid Indian potato (Solanum tuberosum) germplasm - TIWARI, JAGESH K; PANDEY, S K; POONAM, POONAM; CHAKRABARTI, S K; GOPAL, J; KUMAR, VINOD (The Indian Journal of Agricultural Sciences, 2026)
The Ryadg gene derived from Solanum tuberosum ssp andigena provides extreme resistance to PVY. ThePVY resistant potato germplasms tested previously through ELISA were used in present experiment for examining presence/absence of Ryadg gene through linked molecular markers. SCAR and CAPS markers were used as a tool for selecting resistant clones in early generation, to determine the source of resistance and validate the earlier results. Fifty four potato germplasms were screened with molecular markers and by ELISA after mechanical inoculation with PVYO isolate. Eight germplasms validated PVY resistance by containing Ry,adg, gene and negative absorbance value (A405 nm) of ELISA as well. On the contrary, 39 germplasms werefound resistant through ELISA but did not show Ryadg gene. Therefore these 39 resistant germplasms would be the future research materials to identify source of resistance through different molecular markers from wider genetic base of wild potatoes species. Thus, our results demonstrate the application of Ryadg gene linked molecular markers as early, rapid and more reliable technique for the screening of PVY resistance in potato germplasms as an alternative to ELISA.